2017
DOI: 10.1002/ajpa.23338
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic derivation of the Ainu inferred from ancient mitochondrial DNA data

Abstract: ObjectivesThe Ainu, the indigenous people living on the northernmost island of Japan, Hokkaido, have long been a focus of anthropological interest because of their cultural, linguistic, and physical identity. A major problem with genetic studies on the Ainu is that the previously published data stemmed almost exclusively from only 51 modern‐day individuals living in Biratori Town, central Hokkaido. To clarify the actual genetic characteristics of the Ainu, individuals who are less influenced by mainland Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…We also found a considerable genetic affinity between Funadomari Jomons and coastal and marine East Asians (Japanese, Ulchi, Korean, Ami, Atayal, and Hezhen). A recent ancient mtDNA study supported the affinity between Ulchi and Hokkaido Jomon populations, who shared mtDNA haplogroups N9b (4.4% and 64.8%), M7a2 (0.6% and 1.9%), and D4h2 (2.5% and 16.7%) (Adachi et al, 2018); among these, N9b and M7a are considered as Jomon genotypes (Adachi et al, 2009). One Jomon genotype, M7a, is also shared with Korean (3.4%) and Philippines (9.4%) (Tanaka et al, 2004).…”
Section: Ancestral Makeup Of Modern Japanese Archipelago Populationsmentioning
confidence: 89%
See 2 more Smart Citations
“…We also found a considerable genetic affinity between Funadomari Jomons and coastal and marine East Asians (Japanese, Ulchi, Korean, Ami, Atayal, and Hezhen). A recent ancient mtDNA study supported the affinity between Ulchi and Hokkaido Jomon populations, who shared mtDNA haplogroups N9b (4.4% and 64.8%), M7a2 (0.6% and 1.9%), and D4h2 (2.5% and 16.7%) (Adachi et al, 2018); among these, N9b and M7a are considered as Jomon genotypes (Adachi et al, 2009). One Jomon genotype, M7a, is also shared with Korean (3.4%) and Philippines (9.4%) (Tanaka et al, 2004).…”
Section: Ancestral Makeup Of Modern Japanese Archipelago Populationsmentioning
confidence: 89%
“…We identified the geographic origins of the agricultural people as populations related to Korean, She, or Han, as previously described by Jinam et al (2015) and Takeuchi et al (2017). Additionally, previous studies on nonmetric cranial traits (Shigematsu et al, 2004) and modern/ancient DNA analysis (Tajima et al, 2004;Sato et al, 2007Sato et al, , 2009aAdachi et al, 2018) suggested the considerable genetic influence of the aboriginal people of the Lower Amur/Sea of Okhotsk region on Ainu. In the current study, the Ainu was genetically closest to the Funadomari Jomon, but also received gene flow from ancestral populations that inhabited Kamchatka, Lower Amur River region, and far northeast Siberia.…”
Section: Ancestral Makeup Of Modern Japanese Archipelago Populationsmentioning
confidence: 96%
See 1 more Smart Citation
“…The influence of Yayoi on the genetics of people across Japan may vary. The Ainu people in the northernmost Hokkaido, as well as the Ryukyu people who live in the southernmost Ryukyu Islands, are less affected by the Yayoi people (Adachi et al, 2018). They retain more from the Jomons than the Japanese in other regions (Adachi et al, 2018; Crema et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Much later, at the far shallower time depth of the Qín dynasty in the third century BC, this ethnicity spread southward from the Yellow River basin into southern China (Wen et al 2004), where this martial and male-biased historical spread during the cultural sinification of the region south of the Yangtze involved both the spread of language and the introduction of paternal lineages, as historically documented in the Chinese chronicles. The peopling of Japan Our original reconstruction of the peopling of Japan (van Driem 2014), based on earlier genetic research (Kivisild et al 2002;Tajima et al 2004;Tanaka et al 2004;Hammer et al 2006;Jin et al 2009;Karafet et al 2009), has been borne outand can now also be fleshed outby additional work on modern Japanese DNA (Mabuchi et al 2007;Nonaka et al 2007;Yamaguchi-Kabata et al 2008;Nohira et al 2008;Pen and Zhang 2012;Poznik et al 2016) and on ancient Japanese and East Asian DNA (Shinoda 2004;Xue et al 2006;Shinoda and Doi 2008;Adachi et al 2009Adachi et al , 2011Adachi et al , 2013Igawa et al 2009;Kim et al 2011;Jinam et al 2012Jinam et al , 2015Kanzawa-Kiriyama et al 2013;Trejaut et al 2014;Nakagome et al 2015;Yao et al 2017a, c;Adachi et al 2018;Watanabe et al 2019;Gakuhari et al 2019). The synoptic reconstruction presented here and in Figure 5 embodies a number of hypotheses, which may be corroborated or refuted by future ancient DNA findings, or perhaps just require minor reformulation.…”
Section: Austroasiatic Seafarers Set Sail For the Subcontinentmentioning
confidence: 99%